MANAJEMEN BADAN PENANGGULANGAN BENCANA DAERAH KABUPATEN PUNCAK JAYA - irianto; suryaningtyas, dianawati; mardiana, riril (Jurnal Riset Mahasiswa Manajemen, 2025)
Disaster management is a dynamic process, which includes classical management functions. These include planning, organizing, dividing tasks, controlling and supervising. This process involves various organizations working together in carrying out prevention, mitigation, preparedness, emergency response, and post-disaster recovery or reconstruction and rehabilitation processes. This research study aims to describe and explain disaster management at the Puncak Jaya Regency Regional Disaster Management Agency. This research uses qualitative methods to describe and explain disaster management. Data collection techniques in this research were observation, interviews and documentation. The data analysis techniques in this research are information collection, data reduction, data presentation, and the final stage. Data validation techniques in this research are source triangulation, technical triangulation, and time triangulation. The results of this research show that the management of the Regional Disaster Management Agency in Puncak Jaya Regency. (1) that prevention indicators have been carried out well, shown by the many things that have been done, such as early warning, installation of detection equipment, installation of information equipment and so on. (2) mitigation related to disaster management has been going well, as shown by the many mitigation programs carried out such as outreach, training for volunteers or also preparedness programs related to disasters that occurred in Puncak Jaya Regency (3) disaster preparedness is related to disaster management It has been running well, demonstrated by its swift response to the public if a report comes in and it is immediately handled quickly in accordance with Standard Operating Procedures (SOP). (4) the quick reaction regarding Disaster Management has gone well, as shown by the quick response if a disaster occurs and immediately going into the field if there is a report regarding a disaster. The government also prepares personnel and conducts training for volunteers.